Banking Sectors in the new European Union Member States - Marek Stefański (Contemporary Economics)
The main goal of his article is to analyze the economic position and financial strength of banking sectors in the new European Union member states (EU-12). The banking sector consists of all banks that operate in a given country except for the central bank and non-operating banks, such as those in the state of insolvency or liquidation. The author discusses EU-12 banking sectors with regard to a number of economic and financial indices, including the size of assets, the degree of their concentration, ownership types, financial results and efficiency. The analysis is followed by an attempt to evaluate those sectors and assess their financial stability and resistance to macroeconomic and banking risks. Action EU-12 banking sectors in the time of financial crisis is presented as well. Analysis is accompanied by the hypothesis, that about further development of UE-12 banking sectors will decide foreign owners of banks.